Analysis of Demographic Variables and Creativity in Prospective Teachers: A Correlation Study - Singgih, Suwito; Avianti, Gilang Fhadilia; Winarsih, Dwi; Dewi Adila, Agista Sintia (Jurnal Bahasa dan Sastra, 2024)
This study analyzes the influence of gender demographic variables and program creativity on linguistics and science in prospective teacher students. These students must possess creativity, as it enables teachers to create effective and engaging learning experiences. Creativity in the field of science differs from creativity in the field of language. The measurement of linguistic creativity is conducted through a test based on Chomsky's indicators, while scientific creativity is assessed using a test developed by Hu and Adey. A total of 150 research subjects were obtained through random sampling techniques from students enrolled in the Indonesian Language and Literature Education, English Language Education, and Science Education study programs. The study employed a quantitative descriptive method with a correlation approach. Data analysis was carried out using a two-way ANOVA test. The results indicated that the demographic variables related to study program origin had an effect on linguistic creativity, although it was not significant, while they had a significant effect on scientific creativity. The gender demographic variable significantly affected both linguistic creativity and scientific creativity. These findings suggest a need for greater integration of scientific content in language study programs and the incorporation of linguistic activities in science study programs.